Combined Treatment of Wrist and Trapeziometacarpal Joint Arthritis - Waitzenegger, Thomas (J Wrist Surg, 2015)
Background Combined thumb basal and wrist joint arthritis (excluding scaphotrapeziotrapezoid arthritis) is rare considering the frequency of arthritis of either joint alone. Combined surgical treatment has never been described in the literature. Furthermore, the scaphoidectomy common to all interventions for Watson stage 2 or 3 wrist arthritis theoretically makes it impossible to perform a trapeziectomy for thumb basal joint arthritis. Question/Purpose The aim of this study was to present and analyze the results of two types of surgical treatment when both wrist and thumb arthritis was present. Materials and Methods Our retrospective series included 11 patients suffering from Eaton Stage III thumb basal joint arthritis and scapholunate advanced collapse (SLAC) II and III-type wrist arthritis. Five patients (group A) underwent trapeziectomy and palliative surgery for their wrist with conservation of the distal pole of the scaphoid (one proximal row carpectomy [PRC] and four four-corner fusions), and six (group B) patients had a trapeziometacarpal arthroplasty either with PRC (two cases) or four-corner arthrodesis (four cases) including total scaphoidectomy. Results The mean follow-up was 57 months. The overall visual analog scale (VAS) score for pain was 1.5 at rest, with no difference between the trapeziectomy and arthroplasty groups. The average Kapandji score was 9.3 (9 in group A and 9.5 in group B). The flexion/extension range of motion for the wrist was 64° following four-corner arthrodesis and 75° following PRC. Only one case of algodystrophy was observed. The radiological analysis revealed no complications. Discussion This study shows that thumb basal joint arthritis and SLAC type wrist arthritis may be treated by combined treatment during the same intervention without any complications. The results of palliative surgery for the wrist, either with trapeziectomy or with a trapeziometacarpal arthroplasty, are comparable. With a trapeziectomy, the distal pole of the scaphoid must be fused to the capitate to help stabilize the thumb column. Level of Evidence Level IV.